Translation and transcultural validation of a quality of life questionnaire to assess facial cosmetics procedures: a Brazilian Portuguese version - Jaqueline Barbeito de Vasconcellos; Daniela Alves Pereira Antelo; Rosane Orofino-Costa (Sociedade Brasileira de Dermatologia (SBD), 2022)
Background: The increased demand for cosmetic facial treatments is a universal reality, and Brazil is the second country with the most procedures. Quality of life questionnaires can help assess results objectively and reveal data not yet explored in the scientific literature. Thus, the process of translation, adaptation, and validation of questionnaires is necessary for data universalization. Objective: To translate, adapt and validate a specific questionnaire to assess facial cosmetics procedures in Brazilian Portuguese. Methods: After choosing the Skin Rejuvenation Outcome Evaluation (SROE) questionnaire, the translation process started. A literal translation was performed, with the subsequent synthesis of the versions. Then, a team of experts conducted the reverse translation and final validation. The data obtained were statistically analyzed for validation. Results: The final version was called "Avaliação dos Resultados de Rejuvenescimento da Pele" (ARRP). The Cronbach's resulted in values above 0.70, showing good internal consistency. The Intraclass Correlation Coefficient was 0.995 (p<0.001). Conclusions: The values obtained validate the ARRP questionnaire, translated into the Brazilian language and culture, aiming to evaluate the results and impact on the quality of life of facial cosmetics procedures.